2016
DOI: 10.1589/jpts.28.2418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of matrix rhythm therapy on primary lymphedema: a case report

Abstract: [Purpose] Primary lymphedema occurs because of genetic predisposition and developmental insufficiency of the lymphatic system. Matrix Rhythm Therapy was developed as an external and dynamic method that supplies rhythmic mobilization of the fluids in tissues. The aim of the study was to investigate the effects of Matrix Rhythm Therapy in primary lymphedema. [Subject and Methods] A 36-year-old female with left lower limb lymphedema was evaluated. Leg circumference was measured before and at the end of treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…In the current study, we observed muscle soreness in the patient after MRT sessions which might be due to the duration of MRT given;the effects were comparable to a study conducted on frozen shoulder [14]. There were only two previous studies conducted on lymphedema patients, both of which did not mention the exact duration for which MRT was administered [10,15]. Naik et al revealed improved ROM of frozen shoulder and reduction in pain by 30% in VAS just after one sitting of MRT [14].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the current study, we observed muscle soreness in the patient after MRT sessions which might be due to the duration of MRT given;the effects were comparable to a study conducted on frozen shoulder [14]. There were only two previous studies conducted on lymphedema patients, both of which did not mention the exact duration for which MRT was administered [10,15]. Naik et al revealed improved ROM of frozen shoulder and reduction in pain by 30% in VAS just after one sitting of MRT [14].…”
Section: Discussionsupporting
confidence: 79%
“…MRT performed in lymphedema of the limb showed no significant difference in limb volume after 20 sessions given 5 days per week. This might be because the study did not employ CDT in the patient [10]. MRT significantly improves blood flow in areas of its application [11] and increased lymph accumulation might result in production of lymph in edematous tissues or from extrinsic pumping due to vasomotion [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix Rhythm Therapy was created as dynamic and external method of mobilising fluids in tissues. When used alone, Matrix Rhythm Therapy did not decrease lymphedema, but it may be beneficial in the long run (5).…”
Section: Matrix Rhythm Therapymentioning
confidence: 88%
“…Even the research done by Taspinar et al says that MRT, along with massage, increases peripheral blood flow [ 18 ]. Research performed by Narin et al suggests that when MRT is used alone, it is unable to decrease lymphedema; however, if continued therapy is given, it may have beneficial consequences [ 19 ].…”
Section: Discussionmentioning
confidence: 99%